Screening for Thalassemia Carriers in Populations with a High Rate of Iron Deficiency: Revisiting the Applicability of the Mentzer Index and the Effect of Iron Deficiency on Hb A2 Levels. (April 2015) - Amid, Ali; Haghi-Ashtiani, Bahram; Kirby-Allen, Melanie; Haghi-Ashtiani, Mohammad Taghi
Abstract Differentiating between β-thalassemia (β-thal) minor and iron deficiency has important implications in thalassemia carrier screening. Several complete blood count (CBC)-based equations have been proposed for differentiating these two conditions. The applicability of these equations in populations with high rates of iron deficiency and β-thal minor, where patients can have both conditions, is limited. In addition, there have been conflicting reports on the possible effect of iron deficiency on Hb A2 level with possible consequences for thalassemia screening programs. Here, we demonstrate that in our population the Mentzer Index separates individuals with β-thal minor from those without β-thal minor, regardless of their iron status. Iron deficiency also does not reduce Hb A2 levels in β-thal minor patients. Correction of iron deficiency is not required for diagnosis of β-thal minor using high performance liquid chromatography (HPLC).